Nurse prescribing and dispensing in South Africa: Gaps in the current legislative framework - Talitha Crowley; Adrew L. Gray; Nelouise Geyer (AOSIS, 2024)
Background: Nurse prescribing and dispensing are central to ensuring universal health access in South Africa. Objective: To describe the historical development of the legal enablements of nurse prescribing and dispensing in South Africa and highlight gaps in the current legislative framework. Method: This is a discussion article. Results: We emphasise significant deficiencies in the current legislative landscape that pose challenges to these vital nursing practices and call for urgent revisions of the legislative framework, particularly the revision of Section 56 of the Nursing Act (33 of 2005) and its related regulations, to formalise authorisation of specialist nurse prescribers in public and private practice. This will also entail an application to the South African Health Products Regulatory Authority (SAPHRA) for the scheduling of substances by authorised nurse prescribers in the defined professional nurse and specialist nurse categories by the Minister of Health. Conclusion: There is a necessity for prompt legislative revisions to address identified deficiencies. Contribution: The contribution of this article lies in its advocacy for changes to the regulatory framework to further enable nurses to deliver safe and comprehensive health care.